Differentiating metropolitan transport disadvantage by mode: Household expenditure on private vehicle fuel and public transport fares in Brisbane, Australia. (December 2015) - Li, Tiebei; Dodson, Jago; Sipe, Neil
Abstract: Public transport (PT) has become important in everyday travels in Australian cities. Rising PT fares create a competitive disadvantage against private motor vehicles which is threatening PT ridership. This paper seeks to gain further insights into transport disadvantage by exploring spatial patterns of household transport expenditure on PT fares and private vehicle fuel use for the Brisbane metropolitan area. Several datasets are used to measure mode-specific transport costs, including the journey to work matrix, fuel efficiency of the private vehicle fleet and PT fares for the city. Through an advanced spatial analysis, the results show that PT was not a cost-effective means of transport for households when compared to private motor vehicles. The paper then compares mode-specific trip costs with patterns of suburban socio-economic disadvantage in Brisbane. We demonstrate that the high PT fares increase household exposure to higher transport costs and compound other forms of transport disadvantage and vulnerability, particularly in outer suburban areas. Highlights: Public transport was not a cost-effective means of transport for households compared to private motor vehicles in Brisbane. The average private vehicle fuel costs and public transport fares tend to increase as one move further away from the CBD. The high public transport fares increase household exposure to higher transport costs, particularly in outer urban areas.